The Implementation of Self-Regulated Learning Strategies in Promoting Autonomy Learner Among University Students - Santika, Rani; Arifin, Syaadiah; Zulaiha, Siti; Gashimov, Elchin (Publikasi Indonesia, 2025)
Self-regulated learning (SRL) is an essential skill for university students, empowering them to manage their academic endeavors through goal-setting, self-monitoring, and reflection. This study explores the implementation of SRL strategies to promote learner autonomy, focusing on the interplay of technology, culture, and education. Using qualitative methods, the research analyzed data from interviews, observations, and document analysis involving students and educators. Findings reveal that while students excel in goal-setting (75%), engagement in monitoring (60%) and reflection (25%) remains limited, inhibiting the full SRL cycle. Challenges such as unfamiliarity with SRL (60%), poor time management (50%), and inadequate feedback (40%) further hinder adoption. Educators emphasize SRL in feedback and goal-setting (80%) but struggle with embedding it comprehensively in curricula (50%). The study highlights technology's potential to scaffold SRL through tools that enhance feedback, progress tracking, and personalized learning. To foster learner autonomy, the research recommends structured training for students, professional development for educators, and curriculum realignment to address cultural and systemic barriers. These insights aim to advance inclusive, learner-centered environments in higher education